DYNAMIC RESPONSE OF A CRANE STRUCTURE INDUCED BY MOVING TROLLEY WITH SWINGING PAYLOAD - Yazid, Edwar (2009)
A crane system is a machine which characterized by repeating movements such as accelerating, hoisting, traversing and decelerating. The dynamic equations of such system can be considered as an interaction between moving trolley and swinging payload on the crane structure. In this paper, dynamic response of crane structure induced by moving trolley with swinging payload is presented. The crane structure is modeled by using a finite element method, while the moving trolley with swinging payload is represented as rigid-body based on Lagrange’s method. The differential equations of motion are solved numerically using Newmark-b and Runge-Kutta technique simultaneously. Graphical results are presented to show the effect of motion trajectory, either trolley motion or hoist motion to the swinging angles of payload and crane structure response. It is observed that the swinging angle is sensitive to the flexibility of crane structure.